A study to evaluate the impact of patient counselling on the quality of life of female patients with recurrent urinary tract infection - Gopinath, Syama; P. C., Anju; Wesley, I. John; G. R., Prasobh (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Recurrence of urinary tract infections (UTI) are either due to re infection or relapse. Overall likelihood of developing UTI is approximately 30 times higher in women than men due to their anatomical peculiarities and are normally treated with antibiotics. To evaluate effectiveness of patient counselling in prevention of recurrent UTI in female patients to reduce the risk of developing Antibiotic resistance and assess the quality of life of patients. Methods: A prospective observational study was carried out for a period of 6 months and samples were taken from the urology department of cosmopolitan hospital, Trivandrum, Kerala. Patient counseling was given regarding the disease, drugs and lifestyle modifications. A suitably validated KAP questionnaire was provided to each patient at their visits. By using an EQ-5D-5L questionnaire the quality of life of patients were assessed and analyzed. Results: 84 patients were analyzed. After the counseling knowledge level significantly improved to good from 6.9% to 72.4%, the positive attitude level was improved from 35.6 to 57.5% and the practice level was improved to good from 25.3 to 43.7%. The QOL improved to best from 1.2 to 71.4%. After counseling incidence rate was decreased to zero. The mostly observed risk factor was decreased water intake (69%). The common age group observed was 31-50 (41.7%). Conclusions: Patient counseling had an important impact on medication adherence and QOL of female patients with recurrent UTI. Effective patient counseling and better compliance decreased the incidence of recurrence and improved the quality of life of patients.